Evaluating Elementary School Admission Regulations in Indonesia: An SDG 4 Perspective on Equity and Access - Nur Hamidah; Mustaji Mustaji; Bambang Sigit Widodo (Journal of Current Studies in SDGs, 2026)
Objective: This study aims to explore opportunities and challenges in implementing the New Student Admission Policy (PPDB) at elementary schools in Gresik Regency, East Java, Indonesia. It examines how local education authorities manage national regulations in alignment with social, cultural, and geographical contexts. Method: A qualitative approach was used, with data collected through interviews with elementary school stakeholders under the Gresik Regency Education Office. The data were analyzed based on relevant policy concepts and regulations to understand local implementation practices. Results: Successful PPDB implementation depends on local actors’ ability to understand, respond to, and manage complex social and administrative demands. Flexible and locally adapted policies promote equitable access, relevant educational outcomes, and quality services. Effective implementation requires cross-institutional coordination, strong social networks, and community participation. Zoning systems and affirmative policies are crucial to prevent exclusion and ensure schools in low-attractiveness areas receive adequate support. Novelty: This study emphasizes reformulating PPDB policies beyond technical procedures by integrating social values, local culture, and community needs. The findings provide practical guidance for local governments and policymakers to create a more adaptive, inclusive, and sustainable student admission system.